Data supporting "An automated surface determination approach for computed tomography" - Yang, Xiuyuan; Giusca, Claudiu; Sun, Wenjuan (Cranfield University, 2022)
This dataset contains the reconstructed simulation data, MCW surface point clouds, measurement results used for Fig 14 and Fig 16.
Keywords: 'Computed Tomography Imaging Probes'; 'Dimensional Metrology'; 'Watershed'